2021
DOI: 10.2139/ssrn.3997381
|View full text |Cite
|
Sign up to set email alerts
|

Voice Assistants as Gatekeepers for Consumption? - How Information Intermediaries Shape Competition

Abstract: In December 2020, new regulation of digital markets was proposed by European Commission.It specifically addresses main concerns raised by business behavior of operators of core services in their gatekeeping positions. However, voice assistants (or digital personal assistants, DPAs, e.g. Apple's Siri, Amazon's Alexa, Google Assistant) are not included into this regulation. In contrast, the Internal Market and Consumer Protection Committee of European Parliament suggested to include them. This paper argues that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, it has been found that the role of voice assistants is important in the function of a better healthcare system during the global pandemic of COVID-19 globally. Therefore, it can be forwarded that voice assistants are important in the process of the market-based economy and human resources management in the post scenario of the pandemic of COVID-19 [26]. Because the effects of globalization provide a technical challenge for managing the function of a firm in a market-based economy, it has been discovered that the role of voice assistants in marketing and HR is facing many obstacles in the context of mergers and acquisitions [27].…”
Section: Prospectus and Challengesmentioning
confidence: 99%
“…Furthermore, it has been found that the role of voice assistants is important in the function of a better healthcare system during the global pandemic of COVID-19 globally. Therefore, it can be forwarded that voice assistants are important in the process of the market-based economy and human resources management in the post scenario of the pandemic of COVID-19 [26]. Because the effects of globalization provide a technical challenge for managing the function of a firm in a market-based economy, it has been discovered that the role of voice assistants in marketing and HR is facing many obstacles in the context of mergers and acquisitions [27].…”
Section: Prospectus and Challengesmentioning
confidence: 99%